Perbandingan Efektivitas Antipiretik Ekstrak Etanol Daun Kapuk dan Daun Kembang Sepatu Pada Mencit Terinduksi Pepton - Maharani, Silvia; Abeiasa, M. Saka; Yansen, Fatridha (Jurnal Medisains Kesehatan, 2025)
Fever is a physiological response of the body to infection, characterized by an increase in temperature due to the activation of endogenous pyrogens. Herbal plants such as kapok (Ceiba pentandra) and hibiscus (Hibiscus rosa sinensis) are traditionally used as antipyretics due to their active compounds such as flavonoids, tannins, and saponins. This study aims to compare the antipyretic efficacy between ethanol extracts of kapok leaves and hibiscus in mice (Mus musculus) induced with fever using 10% peptone intravenously. The study design was a post-test only control group with 24 white male mice divided into three groups: P1 (negative control, only inducing peptone without treatment), P2 (induced by peptone and given kapok leaf extract 300 mg/kgBW), and P3 (induced by peptone and given hibiscus leaf extract 300 mg/kgBW). Body temperature was measured at 30 to 180 minutes after treatment. The results showed a decrease in average body temperature to 38.1°C at P2 and 36.7°C at P3, while P1's body temperature remained high above 39°C. One-Way ANOVA test showed significant differences between groups (p<0.05). Although both extracts showed significant antipyretic effects, hibiscus extract produced a greater decrease in temperature.